Soil properties and understory herbaceous biomass in forests of three species of Quercus in Northeast Portugal - Castro, Marina (2015)
Aim of study: This paper aims to characterize some soil properties within the first 25 cm of the soil profile and the herbaceous biomass in Quercus forests, and the possible relationships between soil properties and understory standing biomass. Area of study: Three monoespecific Quercus forests (Q. suber L., Q. ilex subsp. rotundifolia Lam. and Q. pyrenaica Willd) in NE Portugal. Material and methods: During 1999 and 2000 soil properties (pH-KCl, total soil nitrogen (N), soil organic carbon (SOC), C/N ratio, available phosphorus (P), and available potassium (K)) and herbaceous biomass production of three forest types: Quercus suber L., Quercus ilex subsp. rotundifolia Lam. and Quercus pyrenaica Willd were studied. Main results: The results showed a different pattern of soil fertility (N, SOC, P, K) in Quercus forests in NE of Portugal. The C/N ratio and the herbaceous biomass confirmed this pattern. Research highlights: There is a pattern of Quercus sp. distribution that correlates with different soil characteristics by soil characteristics in NE Portugal. Q. pyrenaica ecosystems were found in more favoured areas (mesic conditions); Q. rotundifolia developed in nutrient-poor soils (oligotrophic conditions); and Q. suber were found in intermediate zones.